PENERAPAN MANAJEMEN PEMBELAJARAN DI SEKOLAH DASAR SELAMA PANDEMI - Umi Rahmawati, Dwi Nur; Puspita, Ratna Dewi (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2020)
This study aims to reveal how far learning management is carried out by teachers in schools and how learning management is implemented by teachers during the pandemic. This research is Mixed Method research with a sequential explanation method. Samples were taken using a purposive sampling technique. Data collection techniques used questionnaires and data analysis using statistics as an analysis technique followed by interviews and documentation then validated the findings with the Member Checking strategy. The results of statistical analysis of the implementation of learning management based on the function of learning management which includes planning, organizing, mobilizing, and monitoring during the pandemic are categorized as "Medium". This means that the implementation of learning management has not been fully implemented, there are indicators that cannot be met by the teacher in the driving / implementation function. Application of learning management which includes functions; planning, organizing, mobilizing, and supervising teachers according to pandemic conditions. The learning planning function is carried out by preparing learning instruments including syllabus and lesson plans which are prepared by paying attention to distance learning policies; the implementation of the organizing function is carried out with the teacher in coordination with the preparation and implementation of learning with parents; the learning implementing function is carried out with blended learning, the learning evaluation function is carried out through written, oral and practical evaluations that utilize applications on smartphones.